2015
DOI: 10.1016/j.jaerosci.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A methodology to calculate the friction coefficient in the transition regime: Application to straight chains

Abstract: a b s t r a c tA methodology is introduced, the Collision Rate Method (CRM), to calculate the friction coefficient of power-law aggregates across the entire momentum-transfer regime. The friction coefficient is calculated via the ratio of two fictitious particle-aggregate collision rates evaluated in the continuum and slip-flow regimes. The effective collision rates are obtained from the numerical solution of the Laplace equation with Robin boundary condition. The methodology was justified by comparing the sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…(2a) should apply for non-spherical particles (i.e., an expression, which collapses to appropriate continuum and free molecular limits and varies with Knudsen number). By invoking a mass transfer-momentum transfer analogy (i.e., by using a distinct calculation approach from Zhang et al (2012)), Melas, Isella, Konstandopoulos, and Drossinos (2015) additionally have found excellent agreement between the adjusted sphere model and friction factor calculations in the transition regime. Equation (2a) has been recently tested experimentally for flame-synthesized TiO 2 aggregates (Thajudeen, Jeon, & Hogan, 2015), with reasonable agreement found between measurements and equation predictions.…”
Section: Introductionmentioning
confidence: 84%
“…(2a) should apply for non-spherical particles (i.e., an expression, which collapses to appropriate continuum and free molecular limits and varies with Knudsen number). By invoking a mass transfer-momentum transfer analogy (i.e., by using a distinct calculation approach from Zhang et al (2012)), Melas, Isella, Konstandopoulos, and Drossinos (2015) additionally have found excellent agreement between the adjusted sphere model and friction factor calculations in the transition regime. Equation (2a) has been recently tested experimentally for flame-synthesized TiO 2 aggregates (Thajudeen, Jeon, & Hogan, 2015), with reasonable agreement found between measurements and equation predictions.…”
Section: Introductionmentioning
confidence: 84%
“…In the transition regime, the accuracy of this approximation has also been repeatedly verified in various experimental studies (Rogak et al 1993;Chakrabarty et al 2007;Sorensen 2011). Very recently, Melas et al (2015) reported the range of validity of this approximation in the transition regime using the concept of monomer Knudsen number (Kn a D λ/a; not to be confused with Kn). They showed that for Kn a > 2, the projected area approximation held reasonably accurate.…”
Section: Projected Area Approximation In Free Molecular and Transitiomentioning
confidence: 61%
“…A comparison of the predicted diffusion-equivalent spheres to the measured mobility equivalent diameters for a series of nanorods (Gopalakrishnan et al 2015b) showed excellent agreement (Tian et al 2016). Melas et al (2014Melas et al ( , 2015 investigated the friction coefficient and mobility radius of the fractal-like aggregates in the transition regime, and the application to straight chain agglomerates. These studies provided an opportunity to re-examine the high aspect ratio non-spherical particle dynamics, and the development of a convenient equivalent mobility diameter in high Knudsen number flows.…”
Section: Introductionmentioning
confidence: 85%
“…The "adjusted sphere" method has been supported by experiments (Cheng et al 1988;Rogak et al 1993), and most recently validated by Melas et al (2014Melas et al ( , 2015 For majority of the irregular-shaped particles, such as fractal-like agglomerates and straight chains, d adj is not available due to the lack of free molecular information. As a convenience, Equation (4) together with a volume equivalent diameter d ev, is frequently used to approximate the slip correction.…”
Section: Transition Regimementioning
confidence: 99%
See 1 more Smart Citation